ANALISIS TRANSAKSI KREDIT SECARA ONLINE PADA APLIKASI AKULAKU DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM: Studi Pada Mahasiswa IAI AL-AZIS - Faiha Nur Baiti; Irvan Iswandi (Melati Institute, 2022)
Many services are offered to simplify the process of transacting via the internet, ranging from E-Banking, Smart business, bill payments, booking tickets for both planes and cinemas, online loans, and even online credit. The purpose of this study was to determine the practice of buying and selling credit transactions online for Akulaku application users at IAI AL-AZIS students. And to find out the practice of buying and selling credit transactions online for IAI AL-AZIS Students in Positive Law Perspectives and Islamic Law. This study uses a qualitative approach. The approach used in this research is an empirical juridical approach or the sociology of law. The research data sources are primary data sources and secondary data sources. Data collection techniques in this study were observation, interviews and documentation. The results of the study that the practice of online credit transactions for Akulaku application users at IAI AL-AZIS students turned out to include: 1) The first step was downloading the Akulaku application. 2) Registration enter personal data and mobile number via email or telephone. 3) After successfully registered, re-open the application then look for the borrower service menu to see the loan products offered. 4) Select the loan and product type. 5) Fill in the loan nominal and tenor. 6) Enter the account number. 7) Verify the data regarding the loan amount and tenor as well as the fees charged. 8) Voice verification. 9) SMS verification. 10) Selection process. The practice of online credit buying and selling transactions carried out by IAI AL-AZIS students is in accordance with the perspective of Positive Law. The practice of debt and receivables is explained in OJK Regulation Number 77/POJK.07/2016 concerning Information Technology-Based Money Loan Services, which regulates the implementation of Fintech peer to peer lending (P2PL). Meanwhile, in the perspective of Islamic Economic Law, the practice of online debt and credit is allowed with the fulfillment of Islamic law in muamalah.